Analysis of the condition and methods of reconstruction of public buildings - Predun, K.; Gonchar, V.; Kuzmich, Ya.; Shepeta, M.; Verchenko, V. (Ways to Improve Construction Efficiency, 2024)
The reconstruction of public buildings is one of the key directions of modern urban development, combining technical, ecological, and socio-cultural aspects. It plays a crucial role in maintaining the functionality of urban infrastructure, as public facilities provide educational, cultural, administrative, and medical services to society. At the same time, a significant part of this building stock is characterized by a high level of physical and moral deterioration, which necessitates modernization and adaptation to contemporary requirements. This study reveals current trends and approaches to assessing the technical condition of buildings, including visual and instrumental methods, laser scanning, and 3D modeling. The use of these technologies makes it possible to obtain a comprehensive understanding of structural characteristics, detect hidden defects, and evaluate the operational resource of facilities. Particular attention is paid to the application of Building Information Modeling (BIM), which creates a unified digital environment for integrating multi-level information and improves the accuracy of design decisions. Such an approach ensures effective management of reconstruction processes, transparency of stakeholder interactions, and minimization of resource overruns. The study emphasizes the economic and environmental feasibility of reconstruction. The use of local materials, the implementation of energy-saving technologies, the adoption of renewable energy systems, and the application of life-cycle management principles contribute to reducing operating costs and creating an environmentally safe environment. The social and cultural dimension of reconstruction highlights the need to ensure inclusiveness and accessibility, preserve architectural heritage, and reflect local identity. The generalized results confirm that the reconstruction of public buildings is not merely a technical process of restoring functionality. It represents a comprehensive strategy of sustainable development aimed at improving the quality of life of the population, creating an energy-efficient and comfortable urban environment, and ensuring a balance between technical, ecological, and socio-cultural requirements.